ASEAN Outlook on The Indo-Pacific Concerning The Implementation of National Determined Contributions To Achieve Sustainable Development Goal 13 - Wartini, Sri (Padjadjaran Journal of International Law, 2024)
The aim of the research is to analyze comprehensively the ASEAN Outlook on the Indo-Pacific (AOIP) concerning the Implementation of National Determined Contributions (NDCs) to achieve Sustainable Development Goal 13, namely “take urgent action to combat climate change and its impacts”. The bad impacts of climate change do not only cause serious impacts to the environment but also to the economic, social life and culture. International cooperation both regional and universal are important due to an individual state will not be able to overcome the bad impacts of climate change. The ambitious commitment of a single state as a member of the Paris Agreement to reduce emission stipulated in the NDCs should be performed in good faith. Indeed, the success of the NDCs will depend on the commitment of individual state to comply and perform the commitment due to the voluntarily character of the NDCs. The AOIP was formulated to guide cooperation and to create the environment for peace, stability, and prosperity while upholding the rules-based regional architecture. However, the AOIP is not legally binding. The research is a normative juridical research, and the approaches are employed are conceptual approach and statutory approach. The results of this research demonstrates that the implementation of NDCs faces many challenges in the ASEAN and Indo-Pacific which depend on the situation and condition of each state, however, there are some opportunities that can be performed.